Nanotechnology in combating biofilm: A smart and promising therapeutic strategy - Mohanta, Yugal Kishore; Chakrabartty, Ishani; Mishra, Awdhesh Kumar; Chopra, Hitesh; Mahanta, Saurov; Avula, Satya Kumar; Patowary, Kaustuvmani; Ahmed, Ramzan; Mishra, Bibhudutta; Mohanta, Tapan Kumar; Saravanan, Muthupandian; Sharma, Nanaocha (Frontiers in Microbiology, 2023)
Since the birth of civilization, people have recognized that infectious microbes cause serious and often fatal diseases in humans. One of the most dangerous characteristics of microorganisms is their propensity to form biofilms. It is linked to the development of long-lasting infections and more severe illness. An obstacle to eliminating such intricate structures is their resistance to the drugs now utilized in clinical practice (biofilms). Finding new compounds with anti-biofilm effect is, thus, essential. Infections caused by bacterial biofilms are something that nanotechnology has lately shown promise in treating. More and more studies are being conducted to determine whether nanoparticles (NPs) are useful in the fight against bacterial infections. While there have been a small number of clinical trials, there have been several in vitro outcomes examining the effects of antimicrobial NPs. Nanotechnology provides secure delivery platforms for targeted treatments to combat the wide range of microbial infections caused by biofilms. The increase in pharmaceuticals’ bioactive potential is one of the many ways in which nanotechnology has been applied to drug delivery. The current research details the utilization of several nanoparticles in the targeted medication delivery strategy for managing microbial biofilms, including metal and metal oxide nanoparticles, liposomes, micro-, and nanoemulsions, solid lipid nanoparticles, and polymeric nanoparticles. Our understanding of how these nanosystems aid in the fight against biofilms has been expanded through their use.